Analisis Perlindungan Hukum Bagi Pekerja Informal Dalam Perspektif Hukum Ketenagakerjaan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research analyzes the legal protection for informal workers within the framework of labor law in Indonesia. Informal workers, including domestic workers and others in the informal sector, often face legal uncertainty and lack adequate protections compared to formal workers. The study adopts a normative legal analysis method by referencing relevant legislative provisions. The findings indicate that although Law Number 13 of 2003 concerning Manpower provides a legal basis for protecting informal workers, its implementation remains limited. Major challenges include difficulty in identifying informal workers and their lack of awareness regarding their rights. Current protections include the right to fair wages, equitable treatment, and access to social security programs. However, there are legal gaps that need to be addressed to enhance protection for informal workers.